An approach to improve the state scalability of source specific multicast - Al-Talib, Sahar A.; Mohd Ali, Borhanuddin; Khatun, Sabira (Science Publications, 2009)
Problem statement: Source Specific Multicast (SSM) is an acceptable solution for current multicast applications; since the driving applications to date are one to many, including Internet TV, distance learning, file distribution and streaming media. Approach: It was useful for billing, address allocation and security. SSM still had serious state scalability problem when there were a large number of simultaneous on-going multicast groups in the network. Results: In this study, a scheme had been devised to improve the state scalability of source specific multicast. The scheme consisted of two stages: Conclusion/Recommendations: The first stage was to cluster the receivers based on their IP addresses and the second stage was to reduce the multicast state at routers. In order to prove the correctness of the proposed scheme, it had been applied to multicast trees built by other researchers. The results of the comparison approved our statement.